RURAL POLITICAL CLIENTELISM AND ITS IMPACT ON THE VOTING BEHAVIOUR: A PERSPECTIVE OF LANDLESS PEASANTS IN PAKISTAN - Sajid Mahmood Sajid; Dr. Zahira Batool (International Journal of Contemporary Issues in Social Sciences, 2024)
This is a qualitative study in which phenomenon of rural political clientelism has been explored in the context of peasantry in Pakistan. In addition to this, a relationship has been explored between rural political clientelism and voting behaviour of landless peasants. This study has been conducted in district Sargodha of Pakistan. Theory of political clientelism has been used as a theoretical foundation in this study and analogy of patron-client has been applied on the landowner and landless peasants respectively. Findings of the study show that patronage ties are the main determinant of the voting behaviour of the landless peasants in district Sargodha. Mutual exchange relationship of landless peasants with landowner is based on socio-economic inequality, mutual exchange and mutual dependence. Furthermore age, education, media and biradari have little influence on the voting behaviour of the landless peasants in district Sargodha.